2014
DOI: 10.31384/jisrmsse/2014.12.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Occupational Stress on Life Satisfaction among Private and Public School Teachers

Abstract: The study intends to examine the effect of occupational stress on life satisfaction among school teachers. The sample was consisted of 200 school teachers from private and public sector schools of Bhakkar city. Questionnaires are used to assess the response of teachers. Descriptive statistics, Regression analyses and independent sample t-test are used to examine the data. Main findings of the study reveal that higher occupational stress is related to lower life satisfaction ( = .52, p < .001). Significant gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…Our study identified that female respondents perceive more job stress than their male counterparts. Our findings are in line with the study results of Bano and Malik (2014) who concluded that female teachers perceive significantly more stress than male teachers.…”
Section: Discussionsupporting
confidence: 93%
“…Our study identified that female respondents perceive more job stress than their male counterparts. Our findings are in line with the study results of Bano and Malik (2014) who concluded that female teachers perceive significantly more stress than male teachers.…”
Section: Discussionsupporting
confidence: 93%
“…Rode (2004) stated that administrative support, student behavior, school environment, relationship with parents and autonomy affect job satisfaction and that individuals who are satisfied with their jobs tend to be satisfied with their lives. Similar to the result of the current study, there are studies demonstrating that life satisfaction is related to job stress (Bano & Malik, 2014;Barke, 2003;Kumar-Dey and et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…In this process, the individual is expected to evaluate his/her own life rationally and his/her life satisfaction is affected by many factors. It is also known that job satisfaction and life satisfaction are closely related concepts (Bano & Malik, 2014). Blegen (1993) found that age, autonomy, commitment, communication, justice, locus of control, stress, and experience are associated with life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding mental status, an impressive volume of research focused on public school teachers. Bano and Malik (2014) indicated that teachers’ life satisfaction would be low when facing tremendous workplace stress in public or private educational institutions. Unlike teachers in public schools, the SEI tutors as a part of private education were provided by commercial firms, which has the property of market orientation.…”
Section: Introductionmentioning
confidence: 99%